2021
DOI: 10.13057/biodiv/d221220
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of hoverflies (Diptera: Syrphidae) in Nagarjun, Shivapuri Nagarjun National Park, Nepal

Abstract: Abstract. Budhathoki N, Dhakal S, Dyola U. 2021. Diversity of hoverflies (Diptera: Syrphidae) in Nagarjun, Shivapuri Nagarjun National Park, Nepal. Biodiversitas 22: 5382-5388. Hoverflies are recognized as potential pollinators of a wide range of wild plants. This study explored the abundance and diversity of hoverflies over three different seasons from October 2018 to April 2019 in two different study sites, i.e. forest and grassland at Nagarjun of Shivapuri Nagarjun National Park, Nepal. Each site of the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 27 publications
(31 reference statements)
0
9
0
Order By: Relevance
“…reported that syrphids are active throughout the year but with greater prominence in the spring. This distribution is related to the periods in which there is greater availability of oral resources, which are necessary for adult nutrition(Djellab et al 2019;Budhathoki et al 2021).In this study, the mean temperature ranged between 21 and 32°C and had a negative in uence on the abundance and composition of the Syrphidae community. It is noteworthy that there are several possible factors that affect the abundance, including local and site-dependent biological factors; for example, very high temperatures can in uence the oral structure, leaving plants more wilted, which indirectly affects visitation by ies.…”
mentioning
confidence: 68%
See 3 more Smart Citations
“…reported that syrphids are active throughout the year but with greater prominence in the spring. This distribution is related to the periods in which there is greater availability of oral resources, which are necessary for adult nutrition(Djellab et al 2019;Budhathoki et al 2021).In this study, the mean temperature ranged between 21 and 32°C and had a negative in uence on the abundance and composition of the Syrphidae community. It is noteworthy that there are several possible factors that affect the abundance, including local and site-dependent biological factors; for example, very high temperatures can in uence the oral structure, leaving plants more wilted, which indirectly affects visitation by ies.…”
mentioning
confidence: 68%
“…Among the subfamilies collected, Syrphinae had the highest number of species collected (46) and the highest relative frequency (90.27%) (Table 1). (10) captured in both phytophysiognomies with entomological nets. The other species collected accounted for less than 4% of the total collection (Supplementary Material 1, Table S1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Oriental and Palaearctic -NEPAL. Kathmandu District: Manichud at 1,800-2,300m; Nagarjun, 1,400-2,100m; Shivapuri, 1,700-2,300m; Sundarijal, 1,500-2,000m; Nuwakot, Gurjebhanjyang, 1,600-2,000m; Taplejung District: Sanghu at Tumlingtar plateau at 609m, Sankhuwasabha District: Chichila Arun valley; Lalitpur District: Godawari Botanical Garden at 1,400m, Phulchoki at 2,300-2,500m and Hotel Norrbu Linka at 1,350m, Kathmandu District: Thamel, Kritipur, Tribubvan at 1,400m; Kaski District: Ulleri at 2,070-1,800m and Pokhara at 900m, Myagdi: Ghodepani at 2,855m and Sikha at 2,850-1,920m; Dolpa District: Kaigaon to Rimi at 2,800-3,100m, Jumla District at 2,400m and Uthu at 2,500m (Brunetti, 1908;Coe, 1964;Lambeck & Kiauta, 1973;Kapoor et al, 1979;Thapa, 2015;Budhathoki et al, 2021;Dyola et al, 2023).…”
Section: Eristalis (Eoseristalis) Cerealis Fabricius 1805mentioning
confidence: 99%